(untitled) (Journal of the College of Basic Education, 2023)
The current study involved synthesis of several new N-Substituted - 3- chloro -2- azetidinones for 2,4-Diamino-6-phenyl-1,3,5-triazine by two steps. The first step includes preparation of Schiff bases (Al-A6) by condensation of 2,4-Diamino-6-pheny]-1,3,5-triazine with many substituted aldehydes, then the second step includes preparation new six azetidinone compounds (B1-B6) by reaction of chloro acetyl chloride with the prepared Schiff bases in first step. The prepared compounds were characterized by physical properties, FT-IR, UV and some of them by ’H- NMR, "C-NMR spectroscopy were recorded.